CCAMLR Initiatives to Counter Flag State Non-Enforcement in Southern Ocean Fisheries - Baird, Rachel (Victoria University of Wellington Law Review, 2005)
Not all states that have vessels registered under their flag take responsibility for the actions of those vessels and their crews. When enforcement is not carried out by flag states, illegal, unreported and unregulated (IUU) fishing can proliferate and have a serious impact on fish stocks in areas such as the seas around Antarctica. In this article, Rachel Baird evaluates the measures taken by the Commission on the Conservation of Antarctic Marine Living Resources (CCAMLR) to address the issue of IUU fishing. Port state controls, catch documentation schemes, vessel lists and other options are discussed. She concludes that CCAMLR provides some encouraging examples as to how the global problem of IUU fishing may be addressed.